The Attractiveness of Educational Tourism in Religious Tourism is Related to The Contextualization of Halal Tourism (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Halal tourism as a form of embodiment of a destination for Muslims, has a variety of attractions in it which are the value of the tourism business. Educational tourism can be an option as a form of activity that supports Muslim tourists. Especially through religious tourism which has become a destination for religious or pilgrimage tourism. This study uses a qualitative approach, with a literature review study, educational tourism facilities in religious tourism as the embodiment of halal tourism which refers to Muslim tourists. Through the context of university cooperation as a tourism development partner, this research will examine what attractions allow it to be developed in religious tourism destinations. this condition can be a pilot project for the development of halal tourism, the attractiveness of educational tourism is very likely to be realized in religious tourism.